The collaboration between the school and cultural institutions for heritage education: case study - Guillén Peñafiel, Rebeca; Hernández Carretero, Ana María (Clio. History and History Teaching, 2018)
Heritage education is necessary to ensure the protection, respect and sustainability of the assets that constitute our cultural heritage. In this sense, pretending patrimonial awareness should be a common objective for both formal and non-formal education, strengthening cooperation between schools and research and museum institutions. Knowing how the educational, museum and research institutions of the city of Mérida collaborate to educate on cultural heritage is the objective of this work. For this, on the one hand, we interviewed teachers from different educational centers of Primary Education and those responsible for the disclosure departments of heritage institutions and, on the other hand, we met the interest of students from different schools in the city through a simple questionnaire.